Four-component reaction leading to highly functionalized sulfoalkoxy carbonyl compounds1. Issue 23 (21st March 2015) - Sohail, Muhammad; Zhang, Yixin; Sun, Guangwei; Guo, Xin; Liu, Wujun; Liu, Chang; Zhao, Zongbao K.
<x xml:space="preserve">Abstract</x> Four components together: a new paradigm of four component reaction brings α-bromo-β-sulfoalkoxyl carbonyl compounds with good stereocontrol in moderate to excellent yields.